Degradation study of extended-shelf-life pasteurized milk packaging under different aging conditions - Pena, Carlos Alberto Pinheiro; Branciforti, Marcia Cristina (Frontiers in Food Science and Technology, 2025)
This study investigates the degradation behavior of high-density polyethylene (HDPE) rigid packaging with and without an antibacterial additive composed of silver nanoparticles (Ag) supported on silica-ceramic base. The objective was to evaluate the influence of the additive on packaging properties and degradation under soil burial, natural environmental aging, and accelerated aging conditions. The additive, already known to extend the shelf life of pasteurized milk from 7 to 15 days, showed no effect on the mechanical properties, such as Young’s modulus (E), maximum tensile stress (σm), and elongation at break (ɛb), or thermal stability of HDPE in the initial state. No significant degradation occurred under soil burial within the evaluated period. However, susceptibility to degradation was observed after 10 months of natural aging and 12 days of accelerated aging, mainly though reductions in tensile strength and elongation at break. Under natural aging, samples containing the antibacterial additive showed greater loss in deformation at break (99.8%) then neat HDPE (96.0%). Thermal analysis confirmed the deterioration of HDPE after exposure to degradation tests, but the presence of Ag nanoparticles partially preserved polymer stability against UV radiation. These findings indicate that while the antibacterial additive does not hinder HDPE performance during use, it influences its long-term degradation profile, with implications for both product functionality and environmental persistence.